Comparative genomic analysis of plasmids harboring blaOXA-48-like genes in Klebsiella pneumoniae - Li, Wang; Guo, Hengzhao; Gao, Yi; Yang, Xiaofan; Li, Ruirui; Li, Shuangyu; Sun, Chunlong; Du, Wen; Chen, Shaopeng; Xu, Pengpeng; Huang, Wenwen; Shi, Jia; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The emergence and spread of carbapenem-resistant Klebsiella pneumoniae (CRKP) is a serious medical problem worldwide. Acquired OXA-48-like carbapenemases encoded by plasmids are important causes of carbapenem resistance in K. pneumoniae. To explore the links between plasmids and blaOXA-48-like genes in K. pneumoniae, we systematically analyzed the variants of blaOXA-48-like plasmid replicon types, phylogenetic patterns, geographic distribution, conjugative transfer regions, and the genetic environments surrounding blaOXA-48-like of 191 blaOXA-48-like-harboring plasmids, which were identified from 4451 plasmids of K. pneumoniae downloaded from GenBank. Our results showed that seven different variants of blaOXA-48-like genes were identified from the 191 blaOXA-48-like-harboring plasmids in K. pneumoniae, with blaOXA-48, blaOXA-232, and blaOXA-181 being highly prevalent. In K. pneumoniae, blaOXA-48 was mainly carried by the composite transposon Tn1999.2 located on IncL/M-type conjugative plasmids, which were mainly geographically distributed in Switzerland, Germany, and China. In K. pneumoniae, the blaOXA-232 gene was mainly carried by 6.1-kb ColKP3-type mobilizable plasmids, which were mainly isolated in India. In K. pneumoniae, blaOXA-181 was mainly carried by a group of 50-kb ColKP3-IncX3 hybrid conjugative plasmids and a group of small ColKP3-type mobilizable plasmids with lengths of 5.9–9.3 kb, the former was sporadically discovered in China, South Korea, India, and Czech Republic, while the latter was almost all isolated in India. In addition, five blaOXA-245-harboring 65.9-kb IncL plasmids of K. pneumoniae isolated in Spain were found to have the genetic context of blaOXA-245 more complicated than that of blaOXA-48-harboring IncL/M-type plasmids, with two copies of IS1R inserted both upstream and downstream of blaOXA-245-lysR. These findings enhance our understanding of the genetic diversity of blaOXA-48-like-harboring plasmids in K. pneumoniae.